Composite phase diamond material, manufacturing method and application thereof

By heat treatment of the precursor under atmospheric pressure, composite phase diamond (CPD) material with sp2-sp3 composite phase structure was prepared, which solved the problem of insufficient conductivity and mechanical properties of diamond in low-temperature measurement, and achieved low-temperature measurement Production methods with limits of 1mK and cost-effective.

CN119430176APending Publication Date: 2025-02-14CITY UNIVERSITY OF HONG KONG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410981276.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-27
Filing Date
2024-07-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing diamond materials have problems of insufficient conductivity and mechanical properties in low temperature measurements, and traditional production methods are costly and complex.

Method used

Using carbon material with sp2-sp3 composite phase, a composite phase diamond (CPD) material with a negative temperature coefficient and a highly fitted resistance-temperature curve was prepared by heat treatment of the precursor under atmospheric pressure.

Benefits of technology

The low temperature measurement limit of CPD materials is achieved to reach 1mK, maintain the mechanical properties and thermal stability of diamonds, and reduce production costs, and is suitable for the manufacturing of low temperature sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430176A_ABST
    Figure CN119430176A_ABST
Patent Text Reader

Abstract

The present invention relates to a composite phase diamond material comprising an sp3 hybrid region and one or more sp2 hybrid regions wherein the sp2 hybrid region is located in the sp3 hybrid region. The invention also relates to a method of making the composite phase diamond material comprising the steps of providing a precursor comprising a carbon feedstock, providing a polymer-forming composition, and heating the precursor to form the composite phase diamond material. The polymer forming composition includes a polymerizable binder. The invention also relates to a method for temperature sensing, including cryogenic temperature sensing, using a sensor comprising the composite phase diamond.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite phase diamond material, a method for manufacturing the composite phase diamond material, and a use of the composite phase diamond material. Background Art

[0002] Diamond is a naturally occurring material known for its unique properties, such as excellent hardness and thermal conductivity, wide band gap and high stability, which makes it an ideal material for various uses, especially in extreme environments. However, due to the absence of free electrons, diamond exhibits low electrical conductivity. It is challenging to modify the properties of diamond through traditional industrial methods, which severely limits the industrial application of diamond.

[0003] In recent years, some researchers have attempted to improve the conductivity of diamond through existing methods such as doping to make it suitable for practical applications. Although conductive diamond has expanded to promising applications in fields such as chemical and biochemical sensing, environmental degradation, electrosynthesis, electrocatalysis, quantum mechanics, superconductors, medicine, space equipment, and energy storage and conversion, its practical use is limited by difficult and cumbersome mechanical processing and high production costs. In addition, due to its crystal lattice, the process of making diamond conductive usually impairs its mechanical properties and thermal stability.

[0004] Temperature is one of the seven fundamental physical quantities. Low temperature physics is a key field that can help us improve our understanding of the universe, matter, and technology. At temperatures close to absolute zero, matter exhibits a series of unusual and exotic properties that cannot be observed at higher temperatures; these properties are very important in several related fields such as quantum computing, quantum simulation, superfluidity, and Bose-Einstein condensation. The ability to measure temperatures close to absolute zero has driven many advances in low temperature physics and quantum physics. Currently, temperatures at and below millikelvin are measured by characterizing a specific thermal state of the system because no conventional thermometer can measure temperatures at such low levels. Although quantum gases with a temperature of 38pK have been produced in the laboratory, conventional thermometers can only measure temperatures above 20mK. Reducing the temperature measurement limit is important, especially for the practical application of various technologies in the fields of low temperature physics and quantum physics.

[0005] Some sp2 hybridized carbon materials have shown good potential for low-temperature temperature measurement. Compared with diamond, graphite has a softer texture and poorer mechanical properties, making it very easy to peel or damage during use. Diamond's extremely low thermal expansion coefficient, excellent hardness, wide band gap and high hole mobility make it an ideal material for temperature measurement in extreme environments.

[0006] Therefore, there remains a need for an improved carbon material that can be used for low temperature measurements without the disadvantages of existing materials. There is also a need for a low-cost method to produce such conductive diamond without sacrificing the inherent desirable properties of diamond. Summary of the invention

[0007] One aspect of the present invention provides a method having a sp 2 -sp 3 Composite phase carbon materials (i.e., diamond materials) are used to solve the above problems, especially to overcome the bottleneck of low temperature measurement. In addition, the combination of sp2 hybrid phase and diamond can significantly affect the conductivity, band gap and other properties of diamond-based materials. This approach provides insights into the potential applications of diamond in the field of electronics. Diamond materials can be referred to as composite phase diamond (CPD).

[0008] Another aspect of the present invention provides a method for manufacturing CPD via a simple and cost-effective method, which includes heat treating a precursor under atmospheric pressure conditions. The method can prepare CPDs with negative temperature coefficients and highly fitted resistance-temperature (RT) curves. The lowest temperature measurement limit of the CPD is 1mK.

[0009] In addition, CPDs clearly exhibit low sensitivity to magnetic fields and excellent thermal stability, which greatly expands their potential applications as materials for temperature measurement, especially low-temperature temperature measurement. This composite phase structure design has been successfully implemented at various scales. For example, micrometer-scale CPD probes and centimeter-scale 3D-printed CPDs have been developed. CPDs are promising materials for the fabrication of next-generation low-temperature temperature sensors and open up new potential for functional diamond applications.

[0010] One aspect of the present invention relates to a method comprising: 3 hybridized region and one or more sp 2 Composite phase diamond material in hybrid region. sp 2 The hybrid region is located in the sp 3 in the hybrid region.

[0011] In one embodiment, sp 2 The hybrid region is distributed in sp 3 The hybridized region has one or more clusters in the form of spaced apart from each other.

[0012] In one embodiment, the composite phase diamond includes one or more regions of amorphous carbon.

[0013] In one embodiment, at least one of the amorphous carbon regions is adjacent to at least a corresponding one of the sp2 hybridized regions to form a cluster.

[0014] In one embodiment, the cluster is spaced apart from another cluster.

[0015] In one embodiment, the composite phase diamond is sp 3 Hybridized region and sp 2 The interface between the hybrid regions contains irregularities.

[0016] In one embodiment, the composite phase diamond material is electrically conductive.

[0017] In one embodiment, the composite phase diamond material is insensitive to magnetic fields; in particular, the composite phase diamond material is insensitive to magnetic fields at temperatures between about -263°C and about 200°C.

[0018] In one embodiment, the composite phase diamond material comprises:

[0019] Based on the total volume of the composite phase diamond material, about 50 volume % to about 90 volume % of the sp 3 hybrid region and about 10 volume % to about 50 volume % of the sp 2 hybrid region; or

[0020] Based on the total volume of the composite phase diamond material, about 50 volume % to about 70 volume % of the sp 3 hybrid region and about 30 volume % to about 50 volume % of the sp 2 hybrid region; or

[0021] Based on the total volume of the composite phase diamond material, about 50 volume % to about 60 volume % of the sp 3 hybrid region and about 40 volume % to about 50 volume % of the sp 2 Hybridized area.

[0022] In one embodiment, the composite phase diamond material comprises:

[0023] Based on the total volume of the composite phase diamond material, about 50 volume % to about 90 volume % of the sp 3 hybrid region, about 10 volume % to about 50 volume % of the sp 2 hybrid region and about 10 volume % to about 50 volume % of said amorphous carbon region; or

[0024] Based on the total volume of the composite phase diamond material, about 50 volume % to about 60 volume % of the sp 3 hybrid region, about 20 volume % to about 40 volume % of the sp 2 hybrid region and about 10 volume % to about 30 volume % of the amorphous carbon region.

[0025] Another aspect of the present invention relates to a method for making a composite phase diamond material, the method comprising the steps of: a) providing a precursor comprising a carbon feedstock, b) providing a polymer forming composition; and c) heating the precursor and the polymer forming composition to form the composite phase diamond material. The polymer forming composition comprises a polymerizable binder.

[0026] In one embodiment, the method comprises a polymerization step, wherein the polymerizable binder is at least partially polymerized prior to the heating step c).

[0027] In one embodiment, the method comprises a mixing step of mixing the polymer-forming composition with the precursor prior to the polymerization step, ie, before the polymerizable binder is polymerized.

[0028] In one embodiment, the carbon feedstock comprises raw diamond; optionally, wherein the carbon feedstock further comprises amorphous carbon and / or graphite.

[0029] In one embodiment, the carbon feedstock comprises a material selected from the group consisting of raw diamond, amorphous carbon, graphite, and combinations thereof.

[0030] In one embodiment, the heating step c) includes a step of converting a portion of the raw diamonds into graphite flakes, or wherein about 10 volume % to about 50% of the raw diamonds are converted into graphite flakes.

[0031] In one embodiment, the step of converting a portion of the original diamond into graphite fragments comprises the step of converting a portion of the original diamond into amorphous carbon.

[0032] In one embodiment, the polymer-forming composition comprises an initiator.

[0033] In one embodiment, the carbon feedstock is in a form selected from the group consisting of powder, film, bulk, and combinations thereof.

[0034] In one embodiment, the composite phase diamond material is in a form selected from the group consisting of powder, film, bulk, and combinations thereof.

[0035] In one embodiment, the binder comprises an organic binder; or wherein the binder comprises an organic material selected from the group consisting of ammonium polyacrylate, methyl methacrylate, acrylamide, di(propylene glycol) diphenylate, N-hydroxyethyl acrylamide and styrene, and combinations thereof.

[0036] In one embodiment, the initiator includes a photosensitive initiator; or wherein the initiator is selected from the group consisting of: N,N'-methylenebisacrylamide, 2-hydroxy-2-methylpropiophenone, triphenylborane, 1-pyrroline-5-carboxylic acid, 2-hydroxy-2-methyl-1-phenyl-1-propanone, phenylbis(2,4,6-trimethylbenzoyl), diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, and combinations thereof.

[0037] In one embodiment, the initiator comprises two different photoinitiators.

[0038] In one embodiment, the polymer-forming composition further comprises a thickener; or, wherein the thickener comprises a polymer; or, wherein the thickener is water soluble; or, wherein the thickener is free of silicon; or, wherein the thickener is free of metal ions.

[0039] In one embodiment, the thickener is selected from the group consisting of polyacrylamide, sodium carboxymethylcellulose, poly(ammonium acrylate), and polyvinyl alcohol, and combinations thereof.

[0040] In one embodiment, the binder is a water-soluble binder and / or an oil-soluble binder.

[0041] In one embodiment, the initiator comprises a photoinitiator, or wherein the initiator absorbs light having a wavelength of about 245 nm to about 400 nm.

[0042] In one embodiment, the heating step further comprises a sintering step.

[0043] In one embodiment, the heating step is performed at a temperature of about 900°C to about 2200°C or about 900°C to about 1600°C.

[0044] In one embodiment, the heating step is performed in an atmosphere comprising a gas selected from the group consisting of argon, nitrogen, and combinations thereof.

[0045] In one embodiment, the heating step is performed at a pressure of about 1 atm.

[0046] In one embodiment, the heating step comprises a hold time of from about 1 hour to about 300 hours, or from about 1 hour to about 80 hours, or from about 5 hours to about 80 hours.

[0047] In one embodiment, the method includes a processing step including a processing selected from the group consisting of focused ion beam processing, 3D printing, plasma assisted polishing, and combinations thereof.

[0048] Another aspect of the present invention relates to the use of a composite phase diamond material according to embodiments of the present invention or a composite phase diamond material manufactured by a method according to embodiments of the present invention for temperature sensing including cryogenic temperature sensing.

[0049] Another aspect of the present invention relates to a method for temperature sensing, including cryogenic temperature sensing, comprising the steps of: a) providing a sensor comprising a composite phase diamond material according to an embodiment of the present invention or a composite phase diamond manufactured by a method according to an embodiment of the present invention, b) placing the sensor at a location where the temperature is to be measured, and c) obtaining a signal from the sensor corresponding to the temperature at the location.

[0050] Without wishing to be bound by theory, it is believed that the present invention may provide a new type of composite phase diamond material (or composite phase diamond) having sp 3 Hybrid phase and sp 2 Hybrid phase. The composite phase diamond material herein may exhibit one or more properties, such as but not limited to high hardness, high electrical conductivity, high thermal stability, negative temperature coefficient, linear magnetoresistance, etc. The composite phase diamond material has potential applications in a variety of fields, including, for example, temperature sensors, infrared sensors, precision electron probes, high temperature electronic devices, magnetic topological devices, etc. It is believed that the method for preparing the composite phase diamond material is simple and can be applied to a wide range of carbon raw material forms, including, for example, particles, films, bulk single crystals and bulk polycrystalline, thereby showing great versatility. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] The patent or application file contains at least one drawing in color. Copies of the color drawings will be provided by the Office upon request and payment of the necessary fee.

[0052] Figure 1 An image taken by high resolution transmission electron microscopy (HRTEM) and corresponding fast Fourier transform (FFT) and selected area electron diffraction (SAED) images of one embodiment of a CPD material according to the present invention are shown, which images show the nanostructural characteristics of the nanocomposite phase structure;

[0053] Figure 2 is a graph showing the performance of the temperature sensing characteristics of a CPD according to one embodiment of the present invention;

[0054] Figure 3 is a graph showing the performance of the temperature sensing characteristics of a CPD according to one embodiment of the present invention;

[0055] Figure 4 is a graph showing the thermal stability of a CPD according to one embodiment of the present invention;

[0056] Figure 5 is a diagram showing structural features of a CPD according to one embodiment of the present invention;

[0057] Figure 6 shows a nano dual-phase structure of an embodiment of the CPD of the present invention;

[0058] Figure 7 is a comparison chart of the conductivity of a CPD according to an embodiment of the present invention and the conductivity of other conductive diamonds;

[0059] Figure 8 A spectrum analysis diagram showing energy band information of a CPD according to one embodiment of the present invention;

[0060] Fig. 9 A graph showing the performance of the temperature sensing characteristics of a CPD according to one embodiment of the present invention;

[0061] Fig.10 A statistical analysis graph showing the resistance dispersion of a CPD according to one embodiment of the present invention;

[0062] Fig.11 A graph showing the response time of a CPD during a rapid temperature change according to one embodiment of the present invention;

[0063] Fig.12 shows an image of a CPD sample according to one embodiment of the present invention;

[0064] Fig.13 shows resistance-temperature (RT) curves of samples having CPDs of different sizes according to one embodiment of the present invention;

[0065] Fig.14 A diagram showing the stability of CPD under a magnetic field;

[0066] Fig.15 A graph showing the effect of heat treatment conditions on the thermal stability of a CPD according to one embodiment of the present invention;

[0067] Fig.16 A diagram showing the oxidation of pristine diamond at different temperatures;

[0068] Fig.17 A graph showing oxidation of CPD at different temperatures according to one embodiment of the present invention;

[0069] Fig.18 A diagram showing thermal properties of a CPD according to one embodiment of the present invention;

[0070] Fig.19A schematic diagram showing one embodiment of a CPD of the present invention;

[0071] Fig. 20 Shown is a graph comparing the hardness of pristine diamond and CPD produced by one embodiment of the method of the present invention. DETAILED DESCRIPTION

[0072] Unless otherwise specifically stated, all tests herein are conducted under standard conditions including room temperature and test temperature of 25°C, sea level (1 atm.) pressure, pH 7, and all measurements are performed in metric units. In addition, all percentages, ratios, etc. herein are by weight unless otherwise specifically stated. It should be understood that, unless otherwise specifically stated, the material compounds, chemicals, etc. described herein are generally commercial and / or industrial standards that can be obtained from many suppliers around the world.

[0073] As used herein, the term "precursor" refers to a material including a carbon feedstock that reacts to form a composite phase diamond (hereinafter referred to as "CPD") material.

[0074] Composite phase diamond ("CPD") contains sp2-sp3 composite phase. This CPD may also be referred to as dual phase diamond ("DPD");

[0075] The term "organic-coated precursor" may refer to a precursor mixed with a binder. Specifically, the term "organic-coated precursor" may refer to a precursor coated with a polymeric binder.

[0076] One embodiment of the present invention relates to a 3 hybridized region and one or more sp 2 CPD material in the hybrid region. In the present invention, sp 3 Hybridized regions and sp 2 The hybrid regions are all carbon regions, but have different configurations in the corresponding carbon atoms. The CPD materials herein may exhibit one or more properties such as, but not limited to, high hardness, high electrical conductivity, high thermal stability, negative temperature coefficient, linear reluctance, and the like.

[0077] In one embodiment of the present invention, sp 2 The hybrid region is located in the sp 3 hybrid region, and can also be distributed throughout the sp 3 In the hybrid region, it can be considered that sp 2 Hybridized regions were introduced into the sp 3 hybridized regions, thereby forming CPD materials. The dual phase can be considered to be essentially structured to contain sp 3 Hybrid phase and sp 2Without wishing to be bound by theory, it is believed that this feature of the CPD material can distinguish the CPD material from those diamonds of the prior art that do not have a dual phase. Even if there are some diamonds of the prior art that have a dual phase, they may, for example, only have one phase located on the surface of another phase with a fairly clear boundary between them, such as a one-sided boundary line and / or a more regular boundary line with fewer bends and turns. In contrast, the CPD material of the present invention has a sp 3 The sp 2 The characteristics of the hybrid phase can at least bring conductive properties to the CPD material, especially in the whole CPD material, while retaining the sp 3 The basic sp contributed by the hybrid phase 3 structure.

[0078] In one embodiment of the present invention, sp 2 The hybridized regions are in the form of one or more clusters and may be spaced apart from each other. 2 The hybridized regions can be substantially uniformly distributed throughout the sp 3 In other words, sp 2 Some regions of the hybrid phase are located in the sp 3 The interior of the hybrid phase, and sp 2 Some regions of the hybrid phase are exposed to sp 3 The outer surface of the hybrid phase (and therefore the outer surface of the CPD). In some cases, the CPD material includes one or more amorphous carbon regions, wherein at least one of the amorphous carbon regions is adjacent to at least one corresponding one of the sp2 hybridized regions to form a cluster. The cluster can be spaced apart from another cluster.

[0079] It is understood that, in general, CPD only has sp 3 Hybrid phase and sp 2 Hybrid phase. In CPD sp 3 In the hybrid phase, CPD basically has an sp 3 hybrid region, which appears as a continuous region throughout the CPD material. 3 Other terms similar or equivalent to the hybrid region may be used elsewhere in this specification, such as diamond matrix and diamond lattice, depending on the context to which they pertain. 2 In the hybrid phase, CPD has multiple sp 2 hybrid region or multiple graphene regions. 2Other terms similar or equivalent to the hybrid regions may be used elsewhere in this specification depending on the context to which they pertain, such as graphite, graphite flakes, graphite regions, etc. CPDs may also contain an amorphous carbon phase, wherein the CPD has multiple amorphous carbon regions.

[0080] In one embodiment of the invention, the CPD material is electrically conductive.

[0081] In one embodiment of the present invention, the CPD material is insensitive to magnetic fields. Specifically, the CPD material is insensitive to magnetic fields at temperatures above about -263°C, or above about -263°C to about 200°C, or from about -200°C to about 100°C. In addition, it is believed that the CPD material exhibits the characteristics of linear magnetoresistance at temperatures below about -263°C. Without wishing to be bound by theory, it is believed that this allows the CPD material to be used in a magnetic field.

[0082] This CPD material according to an embodiment of the present invention can be conductive and insensitive to magnetic fields. With an initial oxidation temperature increase of more than 200°C and maintaining hardness, the present invention is considered to be an ideal semiconductor material for extreme environments and quantum devices. Compared with traditional methods of high temperature and high pressure processes, the method in the embodiment of the present invention is simpler, cost-effective, and suitable for industrial production. It is believed that the organic coated diamond precursor system can be applied to various forms of carbon raw materials for forming CPD materials.

[0083] In one embodiment of the invention, the CPD material comprises from about 50 volume % to about 90 volume % sp 3 hybrid region and about 10 vol % to about 50 vol % of sp 2 Optionally, the CPD material comprises about 50 volume % to about 70 volume % of sp 3 hybrid region and about 30 volume % to about 50 volume % of sp 2 Optionally, the CPD material comprises about 50 volume % to about 60 volume % of sp 3 hybrid region and about 40 volume % to about 50 volume % of sp 2 Optionally, the CPD material comprises about 50 volume % sp 3 hybrid region and about 50 vol% sp 2 Hybridized area.

[0084] In one embodiment of the present invention, the CPD material comprises from about 50% to about 90% by volume of sp 3 hybrid region, about 10 volume % to about 50 volume % of sp 2hybrid region and about 10 volume % to about 50 volume % amorphous carbon region. Optionally, the CPD material comprises about 50 volume % to about 60 volume % sp 3 hybrid region, about 20 volume % to about 40 volume % of sp 2 hybrid region and about 10 volume % to about 30 volume % amorphous carbon region.

[0085] In the embodiments, "volume %" refers to sp 3 Hybridized region, sp 2 Volume fraction (%) of hybridized region or amorphous carbon region.

[0086] In one embodiment of the present invention, the CPD material comprises from about 50% to about 70% by volume of sp 3 hybrid region and about 30 volume % to about 50 volume % of sp 2 Optionally, the CPD material comprises about 60 volume % to about 70 volume % of sp 3 hybrid region and about 30 volume % to about 40 volume % of sp 2 Hybridized area.

[0087] In one embodiment of the present invention, the CPD material comprises from about 60 volume % to about 70 volume % of sp 3 hybrid region, about 30 volume % to about 40 volume % of sp 2 hybrid region and about 0 volume % to about 10 volume % amorphous carbon region.

[0088] Another embodiment of the present invention is directed to a method of making a CPD material, the method comprising the steps of providing a precursor comprising a carbon feedstock; providing a polymer-forming composition comprising a polymerizable binder; and heating the precursor and the polymer-forming composition to form the CPD material.

[0089] Without wishing to be bound by theory, it is believed that this method is easy to establish and cost-effective. Compared with other conventional methods, the method herein can omit high pressure and high temperature processes.

[0090] In one embodiment of the present invention, the carbon raw material comprises raw diamond. Raw diamond may refer to diamond having essentially only or only sp 3 The raw diamond may be in the form of a powder or a block of single crystal diamond. Optionally, the carbon raw material further comprises amorphous carbon and / or graphite in addition to the raw diamond. Without wishing to be bound by theory, it is speculated that including more than one form of carbon material in the carbon raw material, in particular including raw diamond and one or more other forms of carbon material, may accelerate the formation of the CPD material or improve the quality and performance of the CPD.

[0091] In one embodiment of the present invention, the carbon feedstock comprises a material selected from the group consisting of raw diamond, amorphous carbon, graphite, and combinations thereof.

[0092] In one embodiment of the invention, the method includes a polymerization step, wherein the polymerizable binder is at least partially polymerized before the heating step. The polymerizable binder undergoes a polymerization step before heating. The polymerization step is usually carried out in an oven at a temperature of about 60 to about 150°C, or under UV light irradiation with a wavelength of about 245 to about 400nm. The above conditions applied to the polymerization step may depend on the type of binder used. The polymerization step may be an important process for forming CPD materials. A higher degree of polymerization can lead to better results, such as higher conductivity. However, in order to obtain acceptable results for forming CPD materials, the degree of polymerization does not have to be 100%. For example, the degree of polymerization can be about 1% to about 100%, or about 20% to about 100%, or about 30% to about 100%, or about 40% to about 100%, or about 50% to about 100%, or about 60% to about 100%, or about 70% to about 100%, or about 80% to about 100%, or about 90% to about 100%.

[0093] In one embodiment of the invention, the polymer forming composition is mixed with the precursor prior to the polymerization step or prior to polymerization of the polymerizable binder. This may allow the precursor to be coated with the polymerized binder.

[0094] In one embodiment of the present invention, the polymer-forming composition comprises an initiator. Depending on the binder used, the initiator can initiate or accelerate the polymerization step of the binder.

[0095] The carbon feedstock is believed to be the main carbon source for forming the CPD material. However, it is not intended to completely exclude the possibility that there may be other carbon sources for forming the CPD material besides the carbon feedstock, such as carbon from the initiator, but this possibility is relatively small.

[0096] In one embodiment of the invention, the carbon raw material is in the form of a group selected from powder, film, block and combinations thereof. Depending on the target form of the CPD material and / or the binder and / or initiator to be used, different forms of carbon raw materials can be used. For example, carbon raw material powder can be used to form a CPD material for 3D printing. Bulk carbon raw materials can be used to form bulk CPD materials.

[0097] In one embodiment of the present invention, the CPD material is in a form selected from the group consisting of powder, film, bulk and combinations thereof. CPD materials in different forms have different uses. For example, CPD materials in bulk form can be used as sensing materials, protective covers, electrodes, etc.; CPD materials in powder form can be used as conductive powders or made into conductive probes; CPD materials in film form can be used as display materials.

[0098] In one embodiment of the present invention, the binder comprises an organic binder, or wherein the binder comprises an organic material selected from the group consisting of methyl methacrylate, acrylamide, di(propylene glycol) diphenyl ether, N-hydroxyethyl acrylamide and styrene and combinations thereof. The above binders can be used to form CPD materials. It should be noted that the use of acrylamide shows the best results compared to other binders, because the CPD materials prepared in this way have the highest conductivity.

[0099] In one embodiment of the present invention, the initiator comprises a photosensitive initiator, or wherein the initiator is selected from the group consisting of triphenylborane, 1-pyrroline-5-carboxylic acid, 2-hydroxy-2-methyl-1-phenyl-1-propanone, phenylbis(2,4,6-trimethylbenzoyl), diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, and combinations thereof.

[0100] In one embodiment of the present invention, the polymer forming composition further comprises a thickener. The thickener may include a polymer. The thickener may be water soluble. The thickener may not contain silicon. The thickener may not contain metal ions.

[0101] In one embodiment of the present invention, the thickener is selected from the group of polyacrylamide, sodium carboxymethylcellulose, poly(ammonium acrylate) and polyvinyl alcohol and combinations thereof.

[0102] In one embodiment of the present invention, the polymer-forming composition comprises a crosslinking agent for crosslinking the binder. Optionally, the crosslinking agent comprises N,N'-methylenebisacrylamide.

[0103] In one embodiment of the present invention, the binder is a water-soluble binder and / or an oil-soluble binder. Soluble binders facilitate their uniform dispersion.

[0104] In one embodiment of the present invention, the initiator comprises a photoinitiator, or wherein the initiator absorbs light having a wavelength of about 245 nm to about 400 nm.

[0105] In one embodiment of the invention, the heating step comprises a sintering step.

[0106] In one embodiment of the present invention, the heating step is performed at a temperature of about 900°C to about 2200°C. The heating step performed within this temperature range is conducive to the formation of CPD materials. It is believed that CPD materials will not form at temperatures below 900°C. Temperatures above 900°C are preferred. For example, 2200°C is a preferred temperature.

[0107] In one embodiment of the present invention, the heating step is carried out in an atmosphere comprising a gas selected from the group consisting of argon, nitrogen (N2) and combinations thereof. The gas can be used as a protective atmosphere to avoid unwanted reactions, such as oxidation of the CPD material.

[0108] In one embodiment of the present invention, in addition to the above-mentioned sintering processes or conditions, the sintering step may further include other sintering processes such as vacuum sintering, hot isostatic pressing sintering and spark plasma sintering.

[0109] In one embodiment of the invention, the heating step is carried out at a pressure of about 1 atm. This makes the manufacturing process easier to set up because it does not require high pressure conditions. Without wishing to be limited by theory, it is believed that the method provided herein for processing at normal pressure is more economical and easy, but corresponding methods using high pressure can also be used.

[0110] In one embodiment of the invention, the heating step comprises about 1°C min -1 To about 100℃min -1 heating rate.

[0111] In one embodiment of the present invention, the heating step includes a holding time of about 1 hour to about 300 hours, or about 1 hour to about 80 hours, or about 5 hours to about 80 hours. Longer holding times can lead to better CPD material performance, not only with higher thermal stability, but also with higher conductivity. Larger samples require longer holding times. For example, a block diamond with a size of 5 mm x 5 mm x 1 mm may require a holding time of 60 hours to achieve about 0.5 Scm -1 conductivity.

[0112] In one embodiment of the present invention, the method for manufacturing CPD material comprises a treatment step, which comprises a treatment selected from the group of focused ion beam (FIB) treatment, 3D printing, plasma assisted polishing and a combination thereof. The treatment step may occur after the heating step, in which the CPD material is formed to treat the CPD material just formed. The treatment step may be performed before the heating step to treat the carbon raw material. Depending on its application or subsequent treatment steps, the size of the CPD material can be controlled or changed. For example, the CPD material can be in the form of a powder with a particle size suitable for 3D printing. Preferably, the CPD material is controlled or modified into a suitable size for subsequent FIB processing. Those skilled in the art will appreciate that the CPD material of the above-mentioned size or other suitable size is used for the corresponding treatment step.

[0113] In one embodiment of the present invention, the processing step includes a 3D printing step before the heating step. Before the processing step, the polymer forming composition and the precursor are mixed. The mixture of the polymer forming composition and the precursor is initially cured by exposure to a light source, particularly a UV light source. After the initial curing process, the mixture is sintered in the heating step.

[0114] The method herein may also include additional processes after forming the CPD material. For example, the CPD material so prepared can be processed with FIB technology. FIB is used as a manufacturing technology for forming CPD materials. FIB can be a milling or engraving technology for cutting diamonds. Cutting can be performed by FIB using a "side milling" procedure or a "peeling" procedure. In this way, FIB can act as a subtractive method for reducing the size of CPD materials or trimming CPD materials, while 3D printing can act as a superposition method for increasing the side of CPD materials or building CPD materials. For example, the CPD material so prepared can be used as a semi-finished product to be further processed by, for example, 3D printing to form a target CPD with a desired shape and size. This makes it possible to produce a variety of products ranging from microns to centimeters, expanding the possible range of applications. For example, the diamond so prepared has potential applications in sensors, microelectromechanical systems, supercapacitors, solar cells, quantum devices, and electrocatalysis. In addition, CPD materials can also be used as electronic devices and high-power electronic devices in extreme environments. CPD materials are conductive, magnetic field insensitive and thermally stable.

[0115] result

[0116] It can be considered that CPD is the result of graphitization of diamond. In the prior art, graphitization of diamond is generally considered to be undesirable because it can damage the mechanical properties and thermal stability of diamond. However, CPDs according to embodiments of the present invention have a different structure from those traditional graphitized diamonds in the prior art. CPDs or methods of manufacturing CPDs turn the known disadvantages of graphitization into advantages of CPDs. Specifically, due to the significant differences in material properties between adjacent regions, those traditional graphitized diamonds typically exhibit distinct boundaries, which may damage mechanical properties and thermal stability. In contrast, the CPDs of the present invention exhibit a different structure in which graphite fragments are embedded in the diamond matrix. Specifically, the graphite fragments are relatively uniformly embedded in the diamond matrix. In addition, as Figure 1 As shown in a, graphite fragments (red shaded area) are accompanied by island-like amorphous carbon (yellow shaded area) embedded relatively uniformly in the diamond matrix. The diamond matrix phase (blue shaded area) exhibits an atomic spacing of 0.206 nm, corresponding to the {111} diamond points in the fast Fourier transform (FFT) image ( Figure 1 a, inset). This sp 2 / sp3 The existence of the composite phase structure was also verified by other characterizations, including X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy ( Figure 5 ). The amorphous carbon region with an average size of 3.55 nm (26% volume fraction) exhibits an atomic spacing of about 0.338-0.357 nm. The graphite fragment region with a size of 3.01 nm (17% volume fraction) shows an atomic spacing of 0.338 nm, which corresponds to the graphite fragment {0002} ( Figure 1 aInset). Figure 1 Higher magnification image of the selected dashed area in a ( Figure 1 b) It shows the possibility of phase transition between graphite and diamond. For example, part of diamond may be transformed into graphite. The diamond plane (which is oriented at The axis of the region is directly transformed into <1010> The rectangular {0002} graphite plane of the zone axis ( Figure 1 b, red shaded area 1), which is then transformed into a fingerprint-like {0002} graphene plane ( Figure 1 b, red shaded area 2). This transformation process can be represented as d{111}→g{0002}. The transformation process from diamond to graphite is similar to that from graphite to diamond. In addition, an intermediate amorphous carbon phase may be formed during the phase transformation process ( Figure 1 b, yellow shaded area). Amorphous carbon can continue to transform into graphite fragments to reach a more stable state ( Figure 1 b, red shaded area). Selected area electron diffraction (SAED) images show a broad amorphous carbon halo and The face-centered cubic diamond crystal point of the zone axis ( Figure 1 c). In contrast, the graphite phase is not highlighted in the figure because of its low concentration and its {0002} planes overlap with the amorphous carbon corona. Lower magnification HRTEM images at different locations ( Figure 6 a- Figure 6 c) confirmed that the nanocomposite phase structure exhibits a reproducible intermittent periodic distribution in an area of ​​at least 2 μm in size throughout the sample. In addition, the phase transition process also promotes the generation of uniform and alternating tensile and compressive stress fields ( Figure 6 d). The shoulder peaks observed near the (111) and (220) peaks in the XRD pattern also support the existence of stress fields and nanocomposite phase structures ( Figure 5 a). The composite phase structure and the corresponding stress field may be the main factors for the improvement of diamond's high temperature oxidation resistance.

[0117] The conductivity of CPD plays a crucial role in its application as a thermistor or temperature sensing material. High conductivity is essential to ensure that the sensor operates properly at low temperatures while minimizing self-heating. CPD exhibits 1.2 S cm at room temperature. -1 The excellent electrical conductivity of Figure 7 ). This is due to the large amount of sp 2 Hybridized amorphous carbon and graphite fragments are distributed throughout the diamond matrix. These sp 2 Carbon increases the intrinsic electron transport of CPD. In addition, the coexistence of amorphous carbon and graphite fragments is randomly and uniformly distributed in the sp 3 In other words, amorphous carbon regions and graphite fragment regions coexist, and they are randomly and uniformly distributed within the sp3 hybridized regions. This can further increase the conductivity of CPD by generating percolation paths and forming a conductive network. In addition, sp 2 Phase and sp 3 The interface between the phases has a certain number of defects. These structural irregularities can act as electron scattering centers, contributing to electron mobility and transport enhancement. These form the mechanistic basis for the room temperature conductivity in CPDs. In addition, the band gap and ionization energy of CPDs were determined by UV-Vis diffuse reflectance spectroscopy (UV-Vis DRS) ( Figure 8 a) Ultraviolet Photoelectron Spectroscopy (UPS) Figure 8 b) and photoluminescence spectra (PL) ( Figure 8 c). The band gaps of CPD calculated by UV-Vis DRS and PL are about 1.87 eV and 1.80 eV, respectively. The ionization energy of CPD measured by UPS is 7.84 eV. All these results are lower than the literature value of diamond (band gap value is 5.47 eV, and ionization energy is 81 eV), which is also consistent with the above theory. Figure 2 a shows the RT curve of the CPD sample with an initial resistance of 13.13179 Ω (room temperature). The black curve shows the -1The resistance data points obtained with the cooling rate of . The curve shows a monotonically increasing characteristic over the entire test temperature range, indicating a negative temperature coefficient (NTC). Typically, the resistivity of NTC materials increases dramatically at temperatures close to absolute zero. While this characteristic can enhance the sensitivity of the thermometer, it also limits the thermometer from measuring lower temperatures. In contrast, CPD does not encounter such problems. CPD shows an approximately linear increase in resistance as the temperature decreases from about 400 to 10K, while below 10K, the resistance increases significantly. However, even at temperatures as low as 3K, CPD can maintain very low resistance values, which is an unusual property of semiconductor materials. This property ensures that CPD will not fail due to insulation. The data were fit using a three-phase exponential decay function (Expdec3) and extrapolated to the temperature range of 0-500K (represented by the red curve). The coefficient of determination R of the fitted curve 2 is 0.99999, verifying the goodness of fit of the model. In addition, a dilution refrigerator was used to characterize the resistance change of another CPD sample below 1K. The results are shown in Figure 2 c and Fig. 9 a. The resistance of the CPD also increases monotonically in the temperature range of 40mK-1K without any inflection point or mutation. In addition, when fitted using the Expdec3 function, the RT curve of the CPD below 1K has a similar high R of 0.9978. 2 ( Figure 2 c). The above results show that the physical properties of CPD remain stable as it approaches absolute zero from room temperature. In addition, the conventional residuals, defined as the difference between the predicted resistance value and the experimental resistance value, are mainly within the range of ±0.008 arbitrary units ( Fig.10 a), which shows that the theoretical calibration accuracy of CPD can be as high as 8 mK in the temperature range of 3 to 400 K. When fitting only data corresponding to temperatures below 10 K, the values ​​of the conventional residuals are less than ±0.001 arbitrary units ( Fig.10 b and Fig.10 c). Therefore, CPD can achieve a temperature measurement resolution of 1mK at <10K, which is crucial for the practical application of cryogenic temperature sensors. Figure 2 b), the resistance of the CPD shows a good correspondence with temperature. In addition, data were collected in the range of 2.999-3.001K ( Fig.10 d). The variance and standard deviation of the 842 data points are 5.62547×10 -8 and2.37181×10 -4, indicating that the data distribution is highly concentrated. These data are further divided into two intervals: 2.999≤T<3K and 3≤T<3.001K. The calculation intervals of 95% confidence for the former and the latter are 15.76844-15.76849Ω and 15.76837-15.76841Ω, respectively (Table 1). These two independent confidence intervals confirm that the temperature measurement accuracy of CPD at 3K can reach 1mK. According to the fitting results obtained using the Expdec3 function ( Figure 2 a illustration), the resistance of the sample was calculated to be 16.36614Ω at 2mK and 16.36652Ω at 1mK. The difference between these two predicted values ​​is greater than the difference between the resistance values ​​in the temperature intervals of 2.999-3K and 3-3.001K. This proves that the theoretical detection temperature of CPD can reach 1mK, a level that has not yet been achieved by any existing cryogenic temperature sensor. Fig. 9 b shows the time response of the resistance when the temperature increases from 3 K to 400 K. It demonstrates the excellent stability of CPD during temperature measurement. Figure 2 d compares the temperature measurement range of CPD with other cryogenic thermometers. CPD shows a significant advantage because it can measure temperatures at the mK level. In addition, Fig.11 As shown, the response time from placing the CPD from room temperature into liquid nitrogen until it stabilizes is 3.48 s. The response time for a 90% temperature step change (T 0.9 ) in just 2.04 seconds. This capability could facilitate the transition of quantum computing, quantum simulation, and related technologies from research to practical applications. In addition, CPDs can be synthesized at various scales, for example, micrometer-scale CPD probes fabricated by focused ion beam (FIB) Millimeter-scale bulk CPDs and complex structures with CPDs via 3D printing ( Fig.12 ). These different sized samples are suitable for a variety of applications. Fig.13 The repeatability / reproducibility of CPD samples with different sizes is further demonstrated.

[0118] The presence of magnetic fields greatly limits cryogenic temperature measurements. These magnetic fields induce reversible calibration shifts that result in inaccurate temperature readings. These shifts are temporary, and the sensor returns to its zero-field calibration when the magnetic field is removed. The sensitivity of a sensor to magnetic fields greatly affects its value in applications. Figure 3 a. Figure 3 b and Fig.14 The resistance change of CPD in a magnetic field environment is depicted. Under temperature conditions >14K, CPD is almost insensitive to magnetic field changes ( Figure 3 a. Fig.14). Even at <14K, the magnetoresistance change of CPD is still relatively small. At 2K and in a strong magnetic field of 9T, the resistance change rate of CPD is only about 3% ( Figure 3 a inset). The insensitivity of CPDs to magnetic fields is very important in applications such as nuclear magnetic resonance. In addition, CPDs show linear magnetoresistance under magnetic fields ( Fig.14 ). This feature can simplify the calibration process of temperature sensors in magnetic field environments and endow CPD with potential applications in new quantum linear magnetoresistive devices, especially magnetic sensors.

[0119] Cryogenic temperature sensors are also operated and stored at room temperature or high temperature. The resistance of the temperature sensor may change with the measurement of large temperature differences. This greatly challenges the thermal stability of cryogenic temperature sensors, especially for carbon-based sensors. The inventors studied the inherent thermal stability of CPD ( Figure 4 a) and its resistance change after thermal cycling ( Figure 4 c. Figure 4 d). The oxidation of diamond in air usually includes two processes: direct diamond oxidation and diamond oxidation after graphitization. Graphite and other sp 2 Hybrid carbon materials are usually 3 Hybrid diamonds show higher oxidation sensitivity in air. Therefore, research on improving the oxidation resistance of diamonds usually focuses on strategies to prevent diamond graphitization. The inventors found that by incorporating sp 2 The hybrid carbon phase does not reduce the onset oxidation temperature. On the contrary, sp 2 The presence of the hybrid carbon phase significantly increases the initial oxidation temperature of CPD: the initial oxidation temperatures of pristine diamond and CPD are 948K and 1163K, respectively ( Figure 4 a). Compared with other diamond materials, CPD exhibits higher thermal stability ( Figure 4 b) This finding is consistent with the commonly held belief that sp 2 The presence of hybrid carbon bonds contradicts the view that thermal stability is reduced. It is believed that these abnormal features may be related to the structure of CPD. Compared with traditional graphitized diamond, the microstructural characteristics of CPD are sp 3 Carbon-based (>50% sp 3 Carbon), sp 2 The nanocarbon phase is evenly and discretely distributed. This microstructure avoids the large continuous sp 2 The presence of carbon bonds and the protection of sp 2 The nanocarbon phase is not in direct contact with oxygen, which can inhibit the sp 2 Carbon clusters increase at high temperatures. This study is the first to enhance diamond's resistance to high-temperature oxidation without applying the high-pressure treatment used in previous studies. Fig.15The effects of different heat treatment conditions on the thermal stability of CPD are explained. As the duration of heat treatment increases, the thermal stability of CPD increases significantly, while increasing the heat treatment temperature from 1250 to 1550°C has little effect on the thermal stability of CPD. Currently, there is no clear explanation for this unusual phenomenon. The inventors believe that sp 2 The uniform distribution of hybrid carbon phase in the diamond matrix ( Figure 1 a. Figure 6 b and Figure 6 c) Increases the amount of lattice distortion and stress field in CPD. In addition, sp 2 The carbon phase has a larger thermal expansion coefficient than diamond. These sp 2 The thermal expansion of the nanocarbon phase further increases the internal stress of CPD, which is the main factor in enhancing the high-temperature oxidation resistance of diamond. The SEM images more intuitively show the difference in the oxidation process between the original diamond and CPD ( Fig.16 and Fig.17 ). The presence of these lattice distortions and stress fields enhances the nanoscale properties of diamond, offsets the strength reduction caused by graphitization, and inhibits the graphitization and oxidation processes of diamond in air.

[0120] The significant improvement in high-temperature oxidation resistance demonstrates the excellent thermal stability of CPD. Figure 4 c Comparison of the resistance change between a pristine CPD sample and a sample that was exposed to air for seven days without any protection and then subjected to 10 thermal shocks (77-400K). Although the total resistance of the sample increased slightly after the thermal shock, the rate of change was <0.4%. These results indicate that the CPD exhibits excellent resistance stability in response to temperature changes, consistent with the dynamic response test results ( Figure 4 d). After thermal shock, the RT trend of CPD remains unchanged.

[0121] In summary, the inventors have successfully synthesized CPDs with remarkable electrical properties and thermal stability through a simple method. CPDs have demonstrated their ability and stability as temperature sensing materials in extreme environments, verifying the inventors' original design intentions. The lowest temperature measurement limit of CPDs reaches 1mK, which can contribute to the development of low-temperature physics and quantum physics. In addition, the composite phase structure has a great influence on the properties of diamonds. This nanoscale crystal reconstruction allows diamonds to be transformed from an extremely hard material to a functional material. The successful synthesis of CPDs will open up new avenues for the application of diamonds in precision measurement, quantum computing, medical equipment and space technology.

[0122] method

[0123] Sample synthesis

[0124] The raw diamond was commercially available synthetic diamond powder provided by Tianjian Carbon Material Co., Ltd., China, and belonged to type 1b diamond. Diamond particles (80 μm) were thoroughly mixed with acrylic acid ammonium salt polymer (≥99%), acrylamide (≥99%), N,N'-methylenebisacrylamide (≥99%), 2-hydroxy-2-methylpropiophenone (≥99%), diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (≥99%) and water in a specific weight ratio of 60:3.3:2.4:4:0.24:7.3. A DIW 3D printer (3D printer) from Regenovo Biotechnology Co., Ltd., China was used. Work Station). Printing was performed with a line width of 0.4 mm using closely spaced patterns that can be achieved by the cross-hatch printing method. During the printing process, preliminary curing was completed by exposure to a 365 nm UV lamp. The sample was then dried in an oven (Froilabo, France) at 80 ° C for 4 hours. Subsequently, it was sintered in an argon (Ar) atmosphere at 1250 ° C and atmospheric pressure to obtain CPD. All samples were ultrasonically cleaned in anhydrous ethanol. The sintering process was carried out in a tube furnace (BTF-1700C, ANHUI BEQ EQUIPMENT TECHNOLOGY CO., LTD., China). Unless otherwise specified, the sintering time of the samples shown in the manuscript is 1800 min. "≥99%" refers to the purity of the product, that is, the purity of the product is 99% or higher.

[0125] Structural and phase characterization.

[0126] The microstructure of CPD was studied by HRTEM and SAED using a transmission electron microscope (JEM-2011F, JEOL Ltd., Japan) with an accelerating voltage of 200 kV. In order to depict the distribution of amorphous carbon regions and graphite fragment regions in CPD, pseudo-color calibration was performed on the phase regions of multiple HRTEM images. The corresponding regions were then quantitatively analyzed using the adopted ImageJ to ultimately determine the content of each phase. The background filtered images in Strain++ software were used to characterize the stress field of the nanocomposite phase structure via geometric phase analysis. The stress field of the nanocomposite phase structure was characterized by TEM, a CuK α radiation XRD (Smartlab, Rigaku, Japan), XPS (PHI 5802, PHI, USA) and Raman spectroscopy with an excitation wavelength of 532 nm (alpha300 R, WITec, Germany) were used to characterize the component phase and structure of CPD. Before XPS measurement, a 0.5 nm thick Au coating was sputtered onto the sample to calibrate all spectra by shifting the Au 4f-7 peak to 84.0 eV.

[0127] Property measurement.

[0128] The conductivity of the samples was measured using a four-point probe meter (CXT2665, Changzhou Xinyang Electronic Technology Co., Ltd., China) with a distance of 1.59 mm between the probes. UV-Vis DRS was measured by PerkinElmer Lambda950. The band gap of the CPD was obtained from the absorption spectrum using the Tauc plot method. UPS was measured by Escalab Xi+. A helium discharge lamp (He I, E hν =21.22 eV) to measure the valence band spectrum. The PL spectrum of CPD was measured by Edinburgh FLS1000 with a laser wavelength of 532 nm. TM Physical property measurement system of temperature sensor (Quantum Design DynaCool TM , Quantum Design Inc., USA) was used to measure the resistance of CPD under different temperatures and magnetic fields. A thermal analysis system (TGA / DSC 3+, Mettler Toledo, Switzerland) was used to measure the resistance of CPD under different temperatures and magnetic fields. -1 The high temperature oxidation resistance of CPD was investigated at a heating rate of 20°C to 1000°C in air.

[0129] Supplementary Figures and Tables

[0130] Figure 5Structural features of CPD are shown. a X-ray diffraction (XRD) patterns of pristine diamond and CPD. The left inset shows an enlarged portion of the XRD pattern of CPD in the range of 18°-32° 2θ, showing a weakly broadened peak at about 2θ=26°. This peak can be attributed to the (002) reflection of carbon atoms in a hexagonal crystal arrangement, indicating the presence of an amorphous carbon structure. The middle and right insets show the (111) and (220) peaks of CPD, which show a slight shift of about 0.1°, accompanied by the appearance of a shoulder peak on the left (indicated by a gray arrow). This indicates that the lattice constant of the sample has changed and suggests the possibility of lattice distortion at the nanoscale. Similar phenomena have been reported for nanotwinned diamonds. b Raman spectrum of CPD. The 1332cm-1 Raman line representing the primary Raman line of diamond -1 The peak at corresponds to the sp 3 Symmetric stretching vibration of hybridized carbon atoms. The original diamond is at 8.3 cm -1 The full width at half maximum (FWHM) of the CPD peak is 31.4 cm -1 , which is also considered to be a manifestation of lattice distortion, splitting and rearrangement of diamond crystals. -1 The G band at is sp 2 The characteristic band of the hybrid carbon phase has a FWHM of 120 cm -1 , which also reflects the existence of sp 2 Hybrid carbon phase. 2915cm -1 The peak at is called the D+G peak, which is caused by the valley-to-valley scattering of phonons near the K point, the valley-to-valley scattering of phonons near the K' point, and the valley-to-valley scattering of defects. 2 The appearance of this phenomenon indicates that a large number of sp 2 / sp 3 bond transition. c X-ray photoelectron spectrum of the C1s region of CPD. The deconvoluted peaks at 284.3 and 285.1 eV correspond to the sp 2 Hybridized carbon bonds and sp 3 Hybridized carbon bonds.

[0131] Figure 6 The uniform distribution of the nanostructured dual-phase structure at the micrometer scale is shown. a The size of the nanostructured dual-phase structure prepared by the focused ion beam (FIB) technique is about 2×2 μm. 2 a 8000K magnified image of a thin area of ​​the CPD sample. b and c High-resolution transmission electron microscopy (HRTEM) images of selected areas marked in the FIB sample show the reproducible intermittent periodic distribution of the nanostructured dual-phase. d 3D geometric phase analysis of the background filtered image ( Figure 1b) shows the stress field of the nano-biphasic structure, where tensile stress (white) and compressive stress (black) alternate and meet, corresponding to the diamond and graphite and the amorphous carbon transition zones.

[0132] Figure 7 Shows a comparison of the conductivity of CPD with other conductive diamonds (boron-doped diamond (BDD), nitrogen-doped diamond (NDD), phosphorus-doped diamond (PDD), and hydrogen-terminated diamond (HTD)). In single-crystal diamond, the presence of a large number of strongly bonded carbon atoms (σ-bonds) results in an extremely high activation energy, making it challenging to form n-type diamond by doping with nitrogen or phosphorus. Therefore, diamond doping is usually carried out using the smallest possible particle size. It was found that the conductivity of CPD powder with a particle size of 80 μm reached 1.2 S·cm -1 , while the conductivity of a single-crystal diamond with dimensions of 5×5×1 mm 3 was measured to be 0.05 S·cm -1 .

[0133] Figure 8 Shows the spectral analysis of the band information of CPD: a UV-Vis spectrum. Inset: The UV-Vis graph processed using the Tauc-plot method. The calculated band gap of CPD is 1.87 eV. b UPS energy spectrum. c PL spectrum.

[0134] Fig. 9 Shows the performance of the temperature sensing characteristics of CPD. a The resistance change of CPD from 40 to 800 mK. b The rate of change of the resistance response with time at different temperatures. Here, R0 is the average resistance measured at 3 K.

[0135] Fig.10 Shows the statistical analysis of the resistance discreteness of CPD. a The conventional residuals between the data fitted with the Expdec3 function and the measured data points. b The result of fitting the data measured in the temperature range of 2 - 10 K with a seventh-order polynomial. Red line: Experimental data points; Blue line: Seventh-order polynomial fitting curve. Insert table: Fitting curve parameters and related statistical errors (R 2 ). c The distribution of the conventional residuals corresponding to b. d The statistical analysis of the distribution of the resistance values of CPD obtained at about 3 K. During the dynamic response test, the resistance readings in the interval of 2.999 < T < 3.001 K were recorded and compared with the reference values obtained from a Cernox TM cryogenic temperature sensor. The resistance values were analyzed to calculate the confidence interval, variance, and standard deviation, as shown in Table 1.

[0136] Fig.11 Shows the response time of CPD during rapid temperature changes. a The response time of CPD when cooled from room temperature to liquid nitrogen temperature. b The calculated thermal time constant of CPD.

[0137] The thermal time constant (TTC) is a characteristic constant of the thermistor material response time. The thermal balance equation for an isotropic solid without an internal heat source can be expressed as:

[0138] -ρ·C p VdT = α A (T-T1)dt (1)

[0139] Because the direct measurement data in this article is resistance, and resistance directly corresponds to temperature, all parameters related to T in the above equations are replaced by R:

[0140] -ρ·C p ·VdR=α·A·(R-R1)dt (2)

[0141] In equation (2), A represents the surface area of ​​the sample, ρ is the density of the sample, Cp and V are the specific heat capacity and volume of the sample, respectively. α is the heat transfer coefficient between the sample and the surrounding medium, and it may be affected by various factors, including the shape and size of the sample, the method of contact with the surrounding medium, the form of the medium and the flow rate, etc.

[0142] As the sample moves from air to liquid nitrogen, the resistance changes from R0 to R1. The relationship between t and R at any given moment in the process can be obtained by integrating equation (2), yielding:

[0143]

[0144] where τ is the thermal time constant,

[0145]

[0146] Equation (3) can be further written as:

[0147]

[0148] Taking the natural logarithm of both sides of equation (5), it can be further expressed as:

[0149]

[0150] Obviously, plotting 1n(R1-R) versus t yields a linear relationship where the slope of the line corresponds to Then we get the value of τ. Fig.10 As shown in Figure 1, the curve is not a straight line; instead, it consists of two segments, which is due to the reasons mentioned above. Curve fitting is performed on these two segments separately, and τ1 and τ2 are obtained. τ1 is 5.84 seconds, and τ2 is 0.09 seconds. τ1 is located in the region significantly affected by the intermediate medium (water vapor), causing its value to be greatly overestimated. In contrast, t0.26 It can still be reasonably regarded as the starting point of the step change temperature. Therefore, τ2 has a greater reference value.

[0151] Fig.12 Images of actual CPD samples are shown. a and b Columnar CPD probes prepared via FIB, c CPD sample prepared from (110) single crystal diamond, size 5×5×1 mm 3 d 3D-printed CPD sample, printed from diamond powder with a particle size of 80 μm.

[0152] Fig.13 The RT curves of CPD samples of different sizes are shown: Sample A (8×4 mm 2 )、Sample B(4×4mm 2 ), sample C (8×5mm 2 )、Sample D(10×5mm 2 ) and sample E(5×5mm 2 ). All samples show NTC characteristics. The resistance values ​​in samples of different sizes vary slightly. On the one hand, the differences in resistance are to be expected due to the different sizes of the samples. On the other hand, manual operation inherently introduces various unavoidable error sources, so these variations are understandable.

[0153] Fig.14 The stability of CPD under magnetic field is shown. The resistance of CPD as the applied magnetic field increases from 0 to 9 T at different cryogenic temperatures. At temperatures above 10 K, CPD is almost insensitive to external magnetic field. At 2 K, when the magnetic field exceeds 2 T, the resistance of CPD changes, and CPD exhibits linear magnetoresistance characteristics.

[0154] Fig.15 The effect of heat treatment conditions on the thermal stability of CPD is shown. Thermogravimetric curves of different heat treatment processes. With the increase of heat treatment time, the initial thermal oxidation temperature of CPD increases significantly and reaches the maximum value at 1200min. The effect of heat treatment temperature on the thermal stability of CPD is not significant.

[0155] Fig.16 The oxidation of raw diamond at different temperatures is shown. a 700°C, 3 min. b 900°C, 3 min. c 1000°C, 3 min. d 1000°C, 10 min. e 1000°C, 30 min. f 1100°C, 3 min.

[0156] Fig.17The oxidation of CPD at different temperatures is shown. a 700°C, 3 min. b 900°C, 3 min. c 1000°C, 3 min. d 1000°C, 10 min. e 1000°C, 30 min. f 1100°C, 3 min.

[0157] Fig.18 The thermal properties of CPD are shown. a Thermal expansion coefficient of CPD. b Heat capacity of CPD. According to the Debye model, when the temperature approaches absolute zero, the heat capacity of CPD also approaches zero. According to experimental values, the heat capacity of CPD is less than 0.01 J·K at 25 K. -1 mol -1 The low thermal capacitance and low electrical resistance of the CPD can effectively reduce the self-heating effect during temperature measurement.

[0158] Table 1 Descriptive statistics of the resistance data points collected when CPD was tested at 3K.

[0159]

[0160] Table 2 Cryogenic temperature sensor performance indicators. Except for CPD data, all data are from the public disclosure of Lake Shore Cryotronics, Inc.

[0161]

[0162] Example

[0163] Example 1

[0164] The organic diamond precursor was prepared by mixing diamond powder (particle size of 80 μm) with acrylamide, phenyl bis (2,4,6-trimethylbenzoyl) and ammonium polyacrylate in a mass ratio of 30:5:1:1. Diamond powder served as a carbon raw material, acrylamide served as a binder, phenyl bis (2,4,6-trimethylbenzoyl) served as an initiator, and ammonium polyacrylate served as a thickener. The precursor was processed into a desired shape with a desired thickness by 3D printing, and then cured by ultraviolet light with a wavelength of 345 nm. The required curing time may depend on the size of the sample. For example, smaller samples require a shorter time, while larger samples require a longer time. For example, a 3-layer sample with an area of ​​1 cm x 1 cm can generally be cured within a few seconds. Large-sized and / or multi-layer samples (e.g., samples with more than 10 layers) require layer-by-layer curing. The precursor was cured in a tube furnace at 1500°C at 10°C min -1 The solidified precursor was heated in an argon atmosphere at a heating rate of 1000 nm and a holding time of 3 hours to obtain a 3D printed CPD material sample. A temperature sensor was fabricated from the CPD material.

[0165] Example 2

[0166] The organic coated diamond precursor was prepared by mixing bulk single crystal diamond with methyl methacrylate and polyacrylamide (size 5mm x 5mm x 1mm) in a mass ratio of 5:5:1. Bulk single crystal diamond served as a carbon raw material, methyl methacrylate served as a binder, and polyacrylamide served as a thickener. The precursor was cured by ultraviolet light with a wavelength of 345nm. The precursor was heated at 1200°C with an argon atmosphere at a heating rate of 5°C / min. -1 And the holding time is 60 hours, and a bulk conductive CPD material sample is obtained, such as Fig.12 As shown in the right side of Figure c, the size of the CPD sample is 5mm x 5mm. The CPD material can be used directly as a conductive element.

[0167] Example 3

[0168] For example, the CPD thus prepared may have a resistivity of about 0.893 ohm·cm and a conductivity of 1.119 S / cm.

[0169] Example 4

[0170] Figure 1 a shows a TEM image of an embodiment of the CPD material of the present invention, which shows that the sp 3 Hybrid phase (or sp 3 sp in the hybrid region 2 Hybrid phase (or multiple sp 2 hybrid region). This figure shows the sp 3 The hybrid region 10, which may also be referred to as sp 3 Hybrid diamond region or simply diamond region. sp 3 The configuration of carbon atoms in the hybridized region can be completely or substantially sp 3 Hybrid diamond structure. sp 3 The hybridized regions 10 exhibit an atomic spacing of about 0.206 nm. The figure also shows some island carbon regions 20 (or island carbon clusters) of the CPD material. The island carbon regions 20 may also be referred to as non-diamond regions or (a) non-diamond phases, which means that the configuration of the carbon atoms in the island carbon regions 20 may not be completely or substantially sp 3 Hybrid diamond structure. The island carbon regions 20 are distributed throughout the sp 3 In the hybrid region 10, the island-like carbon regions 20 have different sizes and / or shapes. 3 In the hybrid phase 10 , some of the island-shaped carbon regions 20 are separated from each other, while some of the island-shaped carbon regions 20 may be connected to each other.

[0171] The island carbon region 20 may include sp 2Hybridized region 21 or more sp 2 Hybridized region 21. sp 2 The configuration of carbon atoms in the hybridized region can be completely or substantially sp 2 Hybridized carbon structure, or sp 2 Hybrid graphite structure. sp 2 The hybrid region 21 may be in the form of one or more graphite fragments. 2 The hybridized region 21 may contribute to the electrical conductivity of the CPD material.

[0172] In some embodiments, a CPD may have multiple amorphous carbon regions. 2 In addition to the hybridized region 21, the island carbon region 20 may also include an amorphous carbon region 22. 3 Hybridized region or sp 2 The configuration of the hybrid region is different. The configuration of the carbon atoms in the amorphous carbon region 22 has different coexisting bonding configurations, such as sp 1 、sp 2 and / or sp 3 Hybridized carbon configuration. Figure 1 In a, one of the island-like carbon regions 20 is marked as an example for illustration. The marked island-like carbon region 20 is located at Figure 1 There are other island-like carbon regions adjacent to and separated from the marked island-like carbon region 20, and they have different sizes and shapes. Figure 1 a uses a boundary line to frame and distinguish the island carbon region 20 (and other island carbon regions) from the sp 3 Hybridized region 10. Figure 1 a in blue represents sp 3 Hybridized regions, with amorphous carbon regions in yellow and sp 2 Hybridized region. The island-like carbon region 20 including graphite fragments (marked in red) is relatively uniformly embedded in the sp 3 Hybridized regions (marked in blue). In the island carbon region 20, there may be one or more sp 2 In addition, there are one or more amorphous carbon regions 22. The amorphous carbon region 22 is adjacent to at least one corresponding sp2 hybrid region in the sp2 hybrid region. 3 Hybridized region and sp 2 There are irregularities at the interface between the hybrid regions. In other words, sp 2 The boundaries or surfaces of hybrid regions or clusters are irregular. 2 The hybrid region may include protrusions from its main body and extend to the sp 3 The outer part of the hybrid region.

[0173] In some embodiments, it is preferred that the sp 3 Hybridized region plus sp 2 The fraction (wt%) of the amorphous carbon region has a lower ratio than the fraction (wt%) of the hybrid region. In other words, it is preferred to have fewer amorphous carbon regions in the CPD material.

[0174] Figure 1 c shows a selected area electron diffraction (SAED) image of an embodiment of the CPD material of the present invention. The SAED image shows a broad amorphous carbon halo and face-centered cubic diamond crystal points oriented to the

[112] zone axis. It should be noted that this image is a portion of a cross-sectional view of the CPD material, not the surface, which is important for understanding the concepts of uniform distribution and dual phase (composite phase).

[0175] It should be understood that the foregoing merely illustrates and describes examples in which the present invention may be carried out and that modifications and / or variations may be made thereto without departing from the spirit of the present invention.

[0176] It should also be understood that certain features of the present invention described in the context of separate embodiments for clarity may also be provided in combination in a single embodiment. Conversely, various features of the present invention described in the context of a single embodiment for brevity may also be provided separately or in any suitable sub-combination.

[0177] All references specifically cited herein are hereby incorporated by reference in their entirety. However, citation or incorporation of such references is not necessarily an admission of their appropriateness, citableness, and / or availability as prior art against the present invention.

Claims

1. A composite phase diamond material, wherein the composite phase diamond material comprises sp 3 hybridized region and one or more sp 2 hybrid region, where the sp 2 The hybridized region is located in the sp 3 in the hybrid region.

2. The composite phase diamond material according to claim 1, wherein the sp 2 The hybridized regions are distributed in the sp 3 The hybridized region has one or more clusters in the form of spaced apart from each other.

3. A composite phase diamond material according to claim 1 or claim 2, wherein the composite phase diamond comprises one or more regions of amorphous carbon.

4. The composite phase diamond material of claim 3, at least one of the amorphous carbon regions being adjacent to at least a corresponding one of the sp2 hybridized regions to form a cluster.

5. A composite phase diamond material according to claim 4, wherein the cluster is spaced apart from another cluster.

6. The composite phase diamond material according to claim 1 or 2, wherein the composite phase diamond is 3 The hybridized region and the sp 2 The interface between the hybrid regions contains irregularities.

7. A composite phase diamond material according to claim 1 or 2 which is electrically conductive.

8. The composite phase diamond material according to claim 1 or 2, wherein the composite phase diamond material is insensitive to a magnetic field; in particular, the composite phase diamond material is insensitive to a magnetic field at a temperature of about -263°C to about 200°C.

9. The composite phase diamond material according to claim 1 or 2, comprising: Based on the total volume of the composite phase diamond material, about 50 volume % to about 90 volume % of the sp 3 hybrid region and about 10 volume % to about 50 volume % of the sp 2 hybrid region; or Based on the total volume of the composite phase diamond material, about 50 volume % to about 70 volume % of the sp 3 hybrid region and about 30 volume % to about 50 volume % of the sp 2 hybrid region; or Based on the total volume of the composite phase diamond material, about 50 volume % to about 60 volume % of the sp 3 hybrid region and about 40 volume % to about 50 volume % of the sp 2 Hybridized area.

10. The composite phase diamond material according to claim 3, comprising: Based on the total volume of the composite phase diamond material, about 50 volume % to about 90 volume % of the sp 3 hybrid region, about 10 volume % to about 50 volume % of the sp 2 hybrid region and about 10 volume % to about 50 volume % of said amorphous carbon region; or Based on the total volume of the composite phase diamond material, about 50 volume % to about 60 volume % of the sp 3 hybrid region, about 20 volume % to about 40 volume % of the sp 2 hybrid region and about 10 volume % to about 30 volume % of the amorphous carbon region.

11. A method for producing a composite phase diamond material according to any one of claims 1 to 10, the method comprising the steps of: a) providing a precursor comprising a carbon raw material; b) providing a polymer-forming composition comprising a polymerizable binder; as well as c) heating the precursor and the polymer forming composition to form the composite phase diamond material.

12. A method of producing composite phase diamond material according to claim 11, wherein the method comprises a polymerisation step, wherein the polymerisable binder is at least partially polymerised prior to the heating step c).

13. A method of making a composite phase diamond material according to claim 12, comprising a mixing step of mixing the polymer-forming composition with the precursor prior to the polymerising step.

14. A method of producing a composite phase diamond material according to any one of claims 11 to 13, wherein the carbon feedstock comprises raw diamond; optionally, wherein the carbon feedstock further comprises amorphous carbon and / or graphite.

15. A method of producing a composite phase diamond material according to any one of claims 11 to 13, wherein the carbon feedstock comprises a material selected from the group consisting of raw diamond, amorphous carbon, graphite and combinations thereof.

16. A method of manufacturing a composite phase diamond material according to claim 14, wherein the heating step c) includes the step of converting a portion of the raw diamond into graphite fragments, or wherein about 10 volume % to about 50 volume % of the raw diamond is converted into the graphite fragments.

17. A method of manufacturing composite phase diamond material according to claim 14, wherein the step of converting a portion of the raw diamond into graphite fragments comprises the step of converting a portion of the raw diamond into amorphous carbon.

18. A method of producing a composite phase diamond material according to any one of claims 11 to 13, wherein the polymer-forming composition comprises an initiator.

19. A method of producing a composite phase diamond material according to any one of claims 11 to 13, wherein the carbon feedstock is in a form selected from the group consisting of powder, film, bulk and combinations thereof.

20. A method of manufacturing a composite phase diamond material according to any one of claims 11 to 13, wherein the composite phase diamond material is in a form selected from the group consisting of powder, film, bulk and combinations thereof.

21. A method of manufacturing a composite phase diamond material according to any one of claims 11 to 13, wherein the binder comprises an organic binder; or wherein the binder comprises an organic material selected from the group consisting of ammonium polyacrylate, methyl methacrylate, acrylamide, di(propylene glycol) diphenyl ether, N-hydroxyethyl acrylamide and styrene, and combinations thereof.

22. A method of manufacturing a composite phase diamond material according to claim 18, wherein the initiator comprises a photosensitive initiator; or wherein the initiator is selected from the group consisting of: N,N'-methylenebisacrylamide, 2-hydroxy-2-methylpropiophenone, triphenylborane, 1-pyrroline-5-carboxylic acid, 2-hydroxy-2-methyl-1-phenyl-1-propanone, phenylbis(2,4,6-trimethylbenzoyl), diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide and combinations thereof.

23. A method of producing composite phase diamond material according to claim 18, wherein the initiator comprises two different photoinitiators.

24. A method of manufacturing a composite phase diamond material according to any one of claims 11 to 13, wherein the polymer-forming composition further comprises a thickener; or, wherein the thickener comprises a polymer; or, wherein the thickener is water soluble; or, wherein the thickener is free of silicon; or, wherein the thickener is free of metal ions.

25. A method of manufacturing composite phase diamond material according to claim 24, wherein the thickener is selected from the group consisting of polyacrylamide, sodium carboxymethylcellulose, poly(ammonium acrylate) and polyvinyl alcohol, and combinations thereof.

26. A method of producing composite phase diamond material according to any one of claims 11 to 13, wherein the binder is a water soluble binder and / or an oil soluble binder.

27. A method of producing composite phase diamond material according to claim 18, wherein the initiator comprises a photosensitive initiator, or wherein the initiator absorbs light having a wavelength of about 245 nm to about 400 nm.

28. A method of producing composite phase diamond material according to any one of claims 11 to 13, wherein the heating step further comprises a sintering step.

29. A method of producing composite phase diamond material according to any one of claims 11 to 13, wherein the heating step is carried out at a temperature of about 900°C to about 2200°C or about 900°C to about 1600°C.

30. A method of producing composite phase diamond material according to any one of claims 11 to 13, wherein the heating step is carried out in an atmosphere comprising a gas selected from the group consisting of argon, nitrogen and combinations thereof.

31. A method of producing composite phase diamond material according to any one of claims 11 to 13, wherein the heating step is carried out at a pressure of about 1 atm.

32. A method of producing composite phase diamond material according to any one of claims 11 to 13, wherein the heating step comprises a hold time of from about 1 hour to about 300 hours, or from about 1 hour to about 80 hours, or from about 5 hours to about 80 hours.

33. A method of manufacturing composite phase diamond material according to any one of claims 11 to 13, wherein the method comprises a processing step comprising a process selected from the group consisting of focused ion beam processing, 3D printing, plasma assisted polishing and combinations thereof.

34. A method for temperature sensing, including cryogenic temperature sensing, comprising the steps of: a) providing a sensor comprising a composite phase diamond material according to any one of claims 1 to 10 or a composite phase diamond produced by a method according to any one of claims 11 to 33; b) placing the sensor at a location where the temperature is to be measured; and c) obtaining a signal from the sensor corresponding to the temperature at the location.